2009
DOI: 10.1159/000209294
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Anterior Thalamic Nucleus Lesions Are Not Protective against Seizures in Chronic Pilocarpine Epileptic Rats

Abstract: Aims: To investigate whether anterior thalamic nucleus (AN) lesions are protective against spontaneous recurrent seizures in the chronic phase of the pilocarpine model of epilepsy. Methods: Two groups of rats were treated with bilateral AN radiofrequency thalamotomies or sham surgery 2 weeks after pilocarpine-induced status epilepticus. After the lesions, animals were videotaped from the 2nd to the 8th week after status epilepticus (total 180 h). Results: During the 6 weeks of observation, no differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…So far, the only therapy capable of hindering these events in our series of experiments in the pilocarpine model of epilepsy was AN thalamotomy. 2 This treatment however, did not lead to a significant reduction in seizure frequency in chronic epileptic animals 34 and is known to cause significant memory disturbance. 14,15 Additional investigation to characterize suitable treatment modalities to prevent/block seizure activity with limited adverse effects is still necessary.…”
Section: Discussionmentioning
confidence: 93%
“…So far, the only therapy capable of hindering these events in our series of experiments in the pilocarpine model of epilepsy was AN thalamotomy. 2 This treatment however, did not lead to a significant reduction in seizure frequency in chronic epileptic animals 34 and is known to cause significant memory disturbance. 14,15 Additional investigation to characterize suitable treatment modalities to prevent/block seizure activity with limited adverse effects is still necessary.…”
Section: Discussionmentioning
confidence: 93%
“…The use of deep brain stimulation has not been reported extensively in status epilepticus but it is mentioned in discussions (see for example Robakis & Hirsch, 2006). Data from animal seizure models have indicated that low or high frequency stimulation of the anterior thalamic nucleus can increase seizure threshold and delay the occurrence of status epilepticus following administration of the convulsant pilocarpine (Hamani et al., 2009). However, the same stimulation protocol did not terminate established status epilepticus, indicating that the mechanisms underlying induction and maintenance of status epilepticus differ (Hamani et al., 2009).…”
Section: Targets Of Brain Stimulationmentioning
confidence: 99%
“…Interestingly, electrical stimulation of the ANT was found effective for treating refractory focal epilepsy in a clinical trial , while memory problems were reported as adverse effects (Fisher et al, 2010), which may be in part due to its central connectivity (Child & Benarroch, 2013). In line with the finding from these studies, memory improvement was observed in rats stimulated in the EC during behavioral studies , while memory impairments were retained in rats stimulated in the ANT (Hamani, et al, 2009). DBS effects in the MTT and memory are still unknown.…”
Section: Resultsmentioning
confidence: 69%
“…This seems to be in line with behavioral findings of our unpublished data and previous studies. DBS into the EC reversed the effects of memory loss caused by scopolamine, while DBS into the ANT had memory loss retention (Hamani et al, 2009). It is suspected that the neurons in the VTA had a phenotypic switching from GABA cells to TH cells caused by the environmental factor of DBS into the ANT, but not by DBS in the EC or MTT.…”
Section: Part II Dopamine Memory Deep Brain Stimulation and Hypoxia 1 Dopamine And Deep Brain Stimulation Treatment For Diseases With Memmentioning
confidence: 99%